Pengaruh Sistem Informasi Sumber Daya Manusia (SISDM) Mobile terhadap Kinerja Karyawan - Yudi Permana (Jurnal Ragam Pengabdian, 2026)
As an effort to improve and support an electronic-based acceleration system, BLUD RSUD Bekasi Regency has built, developed and managed personnel applications to meet personnel services. Mobile HRIS plays an important role in improving employee performance by providing easy access to information, improving communication and collaboration, and monitoring performance effectively. The purpose of this study is to analyze the effect of the mobile Human Resources Information System (HRIS) on employee performance at BLUD RSUD Bekasi Regency in 2025. This study used a survey method with a quantitative descriptive and verification approach. The sample size was determined using the Slovin formula, with 258 respondents. The sampling technique used was simple random sampling. Data collection in this study used Google Forms. The instrument used by the researcher was a closed-ended questionnaire with a Likert scale. Data analysis techniques included classical assumption testing, descriptive analysis, and verification analysis using Multiple Linear Regression Analysis. The results of the study indicate that the mobile Human Resources Information System (SISDM) and employee performance at the Bekasi Regency Hospital BLUD are in the very good category. There is an influence of the mobile Human Resources Information System (SISDM) on employee performance at the Bekasi Regency Hospital BLUD.Suggestions for the Bekasi Regency Regional Public Service Agency (BLUD) include designing the mobile SISDM to improve efficiency, allowing tasks such as attendance, leave requests, and performance tracking to be performed mobile, saving time and resources. Rewards are an effective way to improve ASN performance, in the form of recognition, awards, or incentives, which can motivate ASN to work better and achieve organizational targets. Conducting regular evaluations of the use of the mobile SISDM and gathering feedback from employees to identify areas that need improvement and enhancement.